Men, Masculinities, and Infertilities - Allan, Jonathan A. (Routledge, 2022)
Drawing on diverse examples from literature, film, memoirs, and popular culture, Men, Masculinities, and Infertilities analyses cultural representations of male infertility. Going beyond the biomedical and sociological towards interdisciplinary cultural studies, this book studies depictions of men's infertility. It includes fictional representations alongside memoirs, newspaper articles, ethnographies and autoethnographies, and scientific reporting. Works under discussion range from twentieth-century novel Lady Chatterley's Lover to romantic comedy film Not Suitable For Children, and science fiction classic Mr Adam, as well as encompassing genres including blockbuster romance and memoir. Men, Masculinities, and Infertilities draws upon both sociological and popular culture research to trace how the discourse of cultural anxiety unfolds across disciplines. This engaging work will be of key interest to scholars of popular culture studies, gender and women's studies (including queer and sexuality studies), critical studies of men and masculinities, cultural studies, and literary studies.